(3EOGQI GdNWQ hGdJCejf (B/s - (3SdGe, CSGeI YRejs; (3TbjQj, fhQj ehSis ((3YeGf(B: s (3OGQ GdMGeO ddfTQ hGdJhRjY(B, s, 2007)
(3GdNWQ,EOGQI GdNWQ,EOGQI eNGWQ GdeUGQa ef efXhQ JCejfj,GdJCejf,JMOjObSW GdJCejf,GdeHGOF GdbGfhfjI dYbO GdJCejf,hXGFa TQcGJ GdJCejf,EYGOI GdJCejf,JShjb GdNOeGJ GdJCejfjI, JCejf EUGHGJ GdYed,GdJCejf VO CNWGQ Gdfbd,GdJCejf VO CNWGQ GdMQjb,GdJCejf Ydi GdMjGI,GdJCejf VO CNWGQ GdeSDhdjI GdeOfjI,GdeNUUGJ GdafjI aj GdJCejfGJ GdYGeI hJCejfGJ GdMjGI,GdJCejf hGdESdGe,GdJCejf aj GdCQOfs
(3HHdjhZQGajG(B:(3U(B.421-423(3; GdedGMb(B:(3U(B.427-475s
Keywords: (3GdCQOfs; (3GdJCejf(B-(3EOGQI hJfXjes